Determinant factors of stunting in children 2-5 years in West Aceh District, Indonesia - Dewi Sandra Lubis; Aripin Ahmad; Faisal Bin Abdurrahman (AcTion: Aceh Nutrition Journal, 2023)
The prevalence of stunting in children under five years of age in Indonesia, and Aceh in particular, is still very high. This condition affects the quality of human resources and future economic growth. This study examined the determinants of stunting among children under five years of age 24-59 months in West Aceh District, Aceh Province, Indonesia. The research method was a cross-sectional study design, using secondary data from the EPPGBM and PIS-PK data from the Health Center in 2020. The sample comprised 386 families with children under five. Data were collected through documentation studies from PIS-PK data and stunting data from the E-PPGBM data. Family data matching was performed using the National Identity Number (NIN). Statistical analysis was performed using a Multiple Logistic Regression test with 95% confidence interval (CI). The results showed a significant association between exclusive breastfeeding (OR= 2,81; p= 0,010), latrine use (OR=1,73; p= 0,043), and smoking (OR= 1,62; p= 0,022) with the prevalence of stunting. Furthermore, exclusive breastfeeding was a determining factor for the incidence of stunting in toddlers (OR= 2,36; p= 0,010).  In conclusion, exclusive breastfeeding practices are a determinant factor of stunting in children under five in West Aceh, so structured efforts need to be made to increase exclusive breastfeeding coverage by strengthening nutrition counseling and breastfeeding preparation for pregnant women up to two years.